Pendidikan Agama Islam Berwawasan Multikultural dalam Menanamkan Toleransi Beragama Siswa di SMPN 1 Kota Bengkulu - Asri Wahyuni; Qolbi Khoiri; Bakhrul Ulum (Yayasan Darussalam Bengkulu, 2025)
This study aims to knowing and describing multicultural values ​​based on Islamic religious education materials containing tolerance in SMP Negeri 1 Bengkulu city, knowing and describing the tolerance attitude of students in SMP Negeri 1 Bengkulu city. This study uses a qualitative method, with data collection techniques through direct observation in the school environment of SMP Negeri 1 Bengkulu city, interviews with school principals, PAI teachers and several students as well as documentation. As for writing the data used descriptive qualitative method. Based on the results of the study, it can be seen that: Multicultural values ​​are insightful in accordance with the following indicators: first, appreciation of the reality of cultural plurality in society, second, recognition of human dignity and human rights, third, development of the responsibility of the world community, and also tolerance in accordance with 4 indicators: first, appreciation of the reality of cultural plurality in society, second, recognition of human dignity and human rights, third, development of world community responsibility. They can live in harmony in a difference without discriminating against each other.